On the chemical abundances of Miras in custers: V1 in the metal-rich globular NGC 5927 - D'Orazi, Valentina; Lemasle, Bertrand (The astrophysical journal. Part 2, Letters, 2018)
We present the first spectroscopic abundance determination of iron, α -elements (Si, Ca, and Ti), and sodium for the Mira variable V1 in the metal-rich globular cluster NGC 5927. We use high-resolution ( R ∼ 28,000), high signal-to-noise ratio (∼200) spectra collected with WINERED, a near-infrared (NIR) spectrograph covering simultaneously the wavelength range0.91-1.35 μ m. The effective temperature and the surface gravity at the pulsation phase of the spectroscopic observation were estimated using both optical ( V ) and NIR time-series photometric data. We found that the Mira is metal-rich ([Fe/H] = −0.55 ± 0.15) and moderately α -enhanced ([ α /Fe] = 0.15 ± 0.01, σ = 0.2). These values agree quite well with the mean cluster abundances based on high-resolution optical spectra of several cluster red giants available in the literature ([Fe/H] = − 0.47 ± 0.06, [ α /Fe] = + 0.24 ± 0.05). We also found a Na abundance of +0.35 ± 0.20 that is higher than the mean cluster abundance based on optical spectra (+0.18 ± 0.13). However, the lack of similar spectra for cluster red giants and that of corrections for departures from local thermodynamical equilibrium prevents us from establishing whether the difference is intrinsic or connected with multiple populations. These findings indicate a strong similarity between optical and NIR metallicity scales in spite of the difference in the experimental equipment, data analysis, and in the adopted spectroscopic diagnostics.
Gesehen am 22.11.2022